Copper-catalyzed trifluoromethylation of alkenes with an electrophilic trifluoromethylating reagent - Wang, Xiao-Ping; Lin, Jin-Hong; Zhang, Cheng-Pan; Xiao, Ji-Chang; Zheng, Xing (Beilstein Journal of Organic Chemistry, 2013)
An efficient method for the copper-catalyzed trifluoromethylation of terminal alkenes with an electrophilic trifluoromethylating reagent has been developed. The reactions proceeded smoothly to give trifluoromethylated alkenes in good to excellent yields. The results provided a versatile approach for the construction of Cvinyl–CF3 bonds without using prefunctionalized substrates.
Keywords: alkenes; catalysis; copper; electrophilic trifluoromethylating reagent; trifluoromethylation